2022
DOI: 10.3390/ma15113854
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Influence of Selected Fabrics and Stitching on the Strength of Upholstery Covers

Abstract: So far, no coherent and comprehensive method has been elaborated allowing investigation of tensile strength of upholstery seams dedicated to upholstered furniture. Producers of this type of furniture are interested in the assessment of the quality of upholstery material joints, which seems to be particularly important for ensuring the appropriate quality of products. Therefore, the objective of this research was to investigate the influence of the type of material used and the direction of the fabric cut on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The characteristic damage of seam grinning is shown in Figure 5 . The results of our research are comparable with the study [ 12 ], where the seam failure is determined by the direction of the specimen’s die-cut. In both fabric types, the weft and warp are significantly different; hence, the variable form of destruction is closely related to the cutting direction of the samples.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The characteristic damage of seam grinning is shown in Figure 5 . The results of our research are comparable with the study [ 12 ], where the seam failure is determined by the direction of the specimen’s die-cut. In both fabric types, the weft and warp are significantly different; hence, the variable form of destruction is closely related to the cutting direction of the samples.…”
Section: Discussionsupporting
confidence: 90%
“…In the weft direction, with a stitch length of 4 mm and a needle type LR 90, the breaking force was lower by 1.16% (426.36 N) than that of PVC faux leather (431.06 N), which is a statistically non-significant difference. Moreover, the study [ 12 ] confirmed that, in general, the strength of the seam is higher in the warp direction.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation